Distribution of lymphatic vessels in normal and arthritic human synovial tissues. Issue 12 (21st November 2003) - Xu, H; Edwards, J; Banerji, S; Prevo, R; Jackson, D G; Athanasou, N A
Abstract : Objectives: To investigate the distribution of lymphatic vessels in normal, rheumatoid arthritis (RA) and osteoarthritis (OA) synovium. Methods: Synovial tissues from 5 normal controls, 14 patients with RA, and 16 patients with OA were studied. Lymphatic vessels were identified by immunohistochemistry using antibodies directed against the lymphatic endothelial hyaluronan receptor (LYVE-1) and recognised blood vessel endothelial markers (factor VIII, CD34, CD31). Results: Lymphatic vessels were found in all zones of the normal, OA, and RA synovial membrane. Few lymphatic vessels were seen in the sublining zone in normal and OA synovium which did not show villous hypertrophy. However, in both RA synovium and OA synovium showing villous hypertrophy and a chronic inflammatory cell infiltrate, numerous lymphatic vessels were seen in all zones of the synovial membrane, including the sublining zone of the superficial subintima. Conclusions: Lymphatic vessels are present in normal and arthritic synovial tissues and are more numerous and prominent where there is oedema and an increase in inflammatory cells in the subintima, particularly in RA. This may reflect increased transport of hyaluronan and leucocyte trafficking in inflamed synovial tissues.